The Making and Termination of Anglo-Nigerian Defence Pact: A Retrospective Analysis - Enessi, Raliat; Osasona, Shakira (ABUAD Journal of Social and Management Sciences, 2025)
The intricacies of the Anglo-Nigerian Defence Agreement threw up a number of intriguing questions, necessitating a closer interrogation. The Nigerian opposition decried the defence agreement as a neo-colonial scheme that was an obstacle to full independence. The Anglo-Nigerian Defence Pact was an agreement between Nigeria and the United Kingdom that outlined military cooperation shortly after Nigeria gained independence from British Colonial rule. The question is whether the defence agreement transitioned from Imperial rule to informal influence or control. The main argument of this paper is that this was not the case. The study relied on secondary sources of data and the realist theory of international relations. The study concludes that the protests and eventual termination of the pact highlighted the importance of engaging the public and key stakeholders in decisions that affect national sovereignty. Nigeria’s rejection of the pact can be seen as a broader statement about the country's desire to chart its own path on the global stage, free from the influence of former colonial powers.